Effects of Service Learning on Physical Education Teacher Education Students’ Subjective Happiness, Prosocial Behavior, and Professional Learning - Chiva-Bartoll, Oscar; Montero, Pedro Jesús Ruiz; Capella-Peris, Carlos; Salvador-García, Celina (Frontiers in Psychology, 2020)
Purpose This study aims to analyze the effects of a service learning (SL) program on the subjective happiness (SH), prosocial behavior (PB), and professional learning (PL) perceptions of Physical Education Teacher Education (PETE) students as well as to examine the correlations among these variables. Methods The study used a quasi-experimental design of two non-equivalent groups (control and experimental) comparing pre-test and post-test data. The instruments used were the Subjective Happiness Scale, the Prosocial and Civic Competence questionnaire, and the Impact of Service Learning during Initial Training of Physical Activity and Sports questionnaire. Results Data indicated that SL only had a significant influence on SH when the students compared themselves with their peers. On the other hand, the effect of SL on promoting PB and PL perceived was significant in several of their dimensions. Finally, the results showed a greater correlation of the perceived PL with the PB than with the SH. Discussion/Conclusion The results of the study provide educational researchers with valuable information to better understand how SL influences the training of PETE students.